Health and human flourishing : religion, medicine, and moral anthropology - Taylor, Carol (Carol R.); Dell'Oro, Roberto, 1959- (Book collections on Project MUSE., 2006)
"Those who have lamented the moral minimalism of much conventional bioethics should celebrate this splendid volume. Those who have called for 'a richer bioethics' should delight in it. Its attention to the nature of human nature and of human flourishing provides an antidote to the reduction of morality to universal and minimal principles. ... The book is enough to give one hope for the future of bioethics."Allen Verhey, professor of theological ethics, Duke Divinity School.